Profil Bidang Masalah Mahasiswa Tahun Pertama di Universitas Sebelas Maret Surakarta - Fandy Kurniawan; Muh Farozin (JURNAL KONSELING GUSJIGANG, 2019)
This study aims to determine the profile of problem areas for first-year students. The study uses a quantitative approach with descriptive survey types. The number of subjects in this study was 298 of first-year students of the Faculty of Economics, Universitas Sebelas Maret Surakarta determined through simple random sampling technique. Data collection instruments using the Alat Ungkap Masalah UMUM Perguruan Tinggi (AUM UMUM PT), while data analysis techniques use descriptive statistics. The study showed that 15% of first-year students had economic and financial problems, 14% had personal problems, 12% had social relations problems, 12% had physical and health problems, 16% had career and job problems, 9% had time problems free, 7% experienced problems with family relationships, 7% experienced youth problems, 4% experienced religious, value and moral problems, and 4% experienced education and learning problems. The results of the study serve as a basis for formulating guidance and counseling services for the development of potential on first year students in Universitas Sebelas Maret Surakarta.